Las otras memorias de Gio Infante: repensar la homotransfobia y la violencia política en el Perú contemporáneo - Giancarlo Cornejo (Revista de Estudios Sociales, 2023)
Queer activist Gio Infante was one of the most lucid voices of the Peruvian social movements. At the age of 31, Infante’s early death stopped a political and intellectual becoming that deserves to be revisited. Cultivating Gio Infante’s memories is an effort to dispute the problematic desires for social normalization of some LGBTQ subjects and, more importantly, to dare to imagine queer horizons in which their lives are not socially and materially determined by violence. This article offers a close reading of Infante’s essay, “The Other Memories: Persecution, Torture, and Death of Homosexuals During the Internal Armed Conflict” (“Las otras memorias: persecución, tortura y muerte de homosexuales durante el conflicto armado interno”), published in 2013. Infante invites us to nurture painful and subversive memories that allow us to glimpse political and affective anti-racist, feminist and queer coalitions. For Infante, the material conditions for imagining a queer peace do not yet exist in the present. Instead, Infante mobilizes the other memories as an analytic that allows him to open the past’s virtualities, to try to repair political violence’s anonymizing effect. In opposition to homonormative articulations and right-wing political consensuses, Infante tirelessly argues for the need to think critically about the material conditions of production, reproduction, and reification of homotransphobia in the present.